0649 Ultrasound Assessment of Tongue Movement as a Predictor of Response to Hypoglossal Nerve Stimulation (HGNS). (27th May 2020) - Korotun, M; Hahn, S; Quintero, L; Rajan, P; Iakovou, A; Mayo, P; Greenberg, H
Abstract: Introduction: HGNS is an approved therapy for obstructive sleep apnea (OSA). Initial setting of HGNS voltage is based on observation of anterior tongue movement, which may not reflect opening of the retroglossal airway. We developed an ultrasonographic (US) technique to assess tongue movement with HGNS. We correlated US measures of tongue movement at the initial HGNS voltage setting with the AHI determined by PSG/HSAT on HGNS therapy. Methods: Eleven subjects implanted with INSPIRE™ (HGNS) were enrolled at least one month post-implantation. Initial HGNS voltage was determined while awake and semi-recumbent and set to achieve visualized anterior tongue protrusion at a tolerable stimulation voltage. A curvilinear probe (5-2MHz) was placed longitudinally in the submental region at the midline with the indicator pointed anteriorly. Hyoid bone excursion (HBE) with stimulation was used as a marker of base of tongue movement. PSG or HSAT was performed to determine AHI with HGNS. Responders were defined as those with a reduction in AHI ≥ 50% and an AHI <20 events/hr. Results: N=11, 6M, 5F, Age=66.5 ±18.4 years, BMI=27.9 ± 2.7 kg/m 2 . Pre-treatment AHI=38.8 ± 13.4/hr, T-90%=10.5 ± 16.7%. Mean HBE in responders=1.02 ± 0.17cm vs 0.76 ± 0.20cm in non-responders (p=0.006). Best subsets regression analysis performed using post-treatment AHI as the dependent variable and age, BMI, baseline AHI, HBE and HGNS voltage as independent variables showed that HBE (coef. -29.1, p=0.038) and BMI (coef. 2.6, p=0.018) were independent predictors of response. Conclusion: We demonstrated that ultrasound assessment of HBE during HGNS may be a useful tool to predict response to therapy and guide HGNS settings. HBE, rather than voltage, predicted post-treatment AHI. Support: None.